Pattern of UTI in Chronic Kidney Disease: Experience from A Tertiary Care Hospital, Bangladesh - Arjumand, Marina; Ali, Golam Mohammad Tayeb; Dutta, Pradip Kumar; Hassan, Md Habib; Hasan, Kazi Md Abrar; Barua, Biplob Kumar (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Urinary Tract Infection (UTI) is common and higher in prevalence in patients with Chronic Kidney Disease (CKD). To find out the frequency and clinicobacteriological pattern of UTI in CKD patients. Materials and methods: A cross-sectional study was done on 1000 of CKD patients attending Nephrology Department of Chattogram Medical College Hospital (CMCH) a tertiary level hospital in Bangladesh during January to December, 2017. Cleancatch midstream urine samples were collected from study populations irrespective of symptoms. Macroscopic and microscopic examinations were done. Urine samples were then inoculated in Blood agar and Mac’Conkey agar and incubated aerobically at 37 °C for 18-24 hours. Microscopic observations and conventional biochemical tests were done to identify the isolated organisms. Significant growth of organisms in urine was defined as UTI. The isolated organisms were tested for antimicrobial susceptibility by using modified Kirby Bauer technique. Results: The prevalence of UTI was 61.8%. with significant asymptomatic UTI for 28%. Gram-negative organisms were most frequent 564 (93%) with predominant Escherichia coli 399 (64%) followed by Klebsiella 113(18%) and Pseudomonas 39(6%). Among Gram positive isolates, Staphylococcus (6%) was the dominant organism isolated. Regarding antibiotic susceptibility, Gram-negative microorganisms were found to be most sensitive to carbapenem and amikacin whereas Gram-positive microorganisms were most sensitive towards carbapenem, colistin and linezolid. Conclusion: In CKD patients, asymptomatic UTI was detected significantly. E.coli was found to be predominant organisms and resistant towards most of the studied common antibiotics. Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 41-45